Constructing an Axis of Evil: Iranian Memoirs in the “Land of the Free” (American Journal of Islam and Society, 2009)
A major phenomenon in recent decades within Orientalist discourse is the indigenous Orientalism that can be seen in the works of some scholars, writers, and thinkers. These writers are sometimes referred to as “captive minds,” “brown sahibs,” or what Malcolm X would call the “houseNegro.”1 Defined by their intellectual bondage and dependence on the West and, at times, likened to pop psychologists in their writings about the “natives,” their western counterparts believe them because, as native informants, they are seen to be in a position to produce authentic representations of the Oriental psyche. This paper offers a brief study of memoirs written by members of the Iranian diaspora in western countries over the past decade, particularly in the United States. Among these writers are Azar Nafisi, Marjane Satrapi, Roya Hakakian, Afshin Molavi, and Azadeh Moaveni, and others. A few books with thriller-like titles, such as Prisoner of Tehran (Marina Nemat: 2008) or Living in Hell (Ghazal Omid: 2005), will not be studied. In the eyes of many Iranian intellectuals, such writers are often viewed as examples of the Iranian intellectual comprador class or members of the gharbzadeh (a term made current by JalalAle-Ahmad, the Iranian critic and intellectual, that can be rendered in English as westernized, west-struck, or westomaniac), rather than as intellectuals.